(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Sannipata Bhairava Rasa is an Ayurvedic formulation quoted in Bhaishajya Ratnavali Jwaradhikara used in the treatment of Jwara (fever). There is no scientific documentation regarding the standard method of preparation and analytical profile of Sannipata Bhairava Rasa. The aim of the study is to prepare Sannipata Bhairava Rasa and analyse it using various physico-chemical methods. Sannipata Bhairava Rasa was prepared as per the classical reference in Bhaishajya Ratnavali. During the pharmaceutical procedure, all the ingredients were taken as per reference, mixed uniformly and triturated with Nimbu swarasa (lemon juice) to make Vati of one Ratti (125mg). Medicines prepared in the form of tablet or pills are known as Vati or Gutika. The physico– chemical and microbial analysis of the prepared formulation was carried out. The pharmaceutical and analytical parameters were compiled, and data was recorded. The values of physico-chemical parameters of Sannipata Bhairava Rasa were as follows- total ash 11.16%, acid insoluble ash 0.63%, alcohol soluble extractive 7.68%, water soluble extractive 20.56%, loss on drying 6.34%. Data generated from pharmaceutical, analytical studies and TLC can be used to develop a preliminary standard profile for the formulation Sannipata Bhairava Rasa.